Chorea: a study of 100 cases - McMillan, J. J. (The University of Edinburgh, 1909)
The material upon which this thesis is founded consists of 100 cases of Chorea that have been studied by me in hospital practice.

DEFINITION: Chorea is a spasmodic affection of the Nervous System characterised by involuntary movements, which are sudden, jerky and irregular, and by a variable degree of muscular weakness accompanied by in-coordination of voluntary movements, and by psychical disturbances usually of the nature of habetude and mental weakness; to these may be added phenomena of arthritis and endocarditis. (Allbutt's System of Medicine.)